Water Use Dynamics of Drought-Tolerant ConiferousTrees (Pinus brutia and Cupressus sempervirens) ina Semi-Arid Environment - Djuma, Hakan; Eliades, Marinos; Zoumides, Christos; Bruggeman, Adriana (My University, 2025)
Pinus brutia (pine) and Cupressus sempervirens (cypress) are two important forestry species in the Mediterranean region, with different strategies to cope with water stress. The overall goal of this study is to investigate ecohydrological processes of these two species. Specific objectives are (i) to quantify differences in sapflow of P. brutia and C. sempervirens trees during wet and dry seasons; (ii) to analyse effects of environmental variables on sapflow, leaf conductance (gs) and twig water potential (Ψ); and (iii) to analyse water balance components and soil water dynamics for three canopy cover conditions (under canopy, edge canopy and open area). The study site is a mixed forest in Cyprus, with an average annual rainfall of 315 mm. The site was planted in 2011 (average planting area: 30 m2). Observations of sapflow (4 trees for 24 months and 8 trees for 20 months) and soil moisture (66 sensors, 24 months) were made hourly. Soil moisture sensors were installed in three canopy cover conditions, each at 10-, 30-and 50-cm soil depths. The sapflow over the canopy area of the trees during the November 2020 to June 2022 period was 642 mm for cypress and 314 mm for pine, under 581 mm rain. The partial correlation coefficient between daily sapflow and soil moisture was higher for pine than for cypress (0.66 vs. 0.31). Pine had a wider range of gs values and narrower range of Ψ values than cypress. Evapotranspiration from the open area was 14% higher than from under the tree canopy.
Keywords: Cupressus sempervirens; drought tolerant trees; evapotranspiration; Mediterranean mixed forest; Pinus brutia; sap flow; soil water; water balance